(3EceGd GdeYde HahGFO (B" (3eSde (B"s - (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s; (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf,J (B261 (3g` s
(3ChdgG (B:s
(3jHJOF HChd GdcJGH s
(3BNQgG (B:s
(3hjfJgi HBNQ CMGOjK GddYGf s
(3Vef eLehY , JQJjHgG (B: (3GdeLdO GdChds
(3GdfSNI HgG MhGTs
(3gPg GdeLdOI JMJhi Ydi KdGKI CLRGA ef JLRFI GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdMOjK h GdeUWdMs